Kajian Penggunaan Antihipertensi dan Potensi Interaksi Obat Pada Pengobatan Pasien Hipertensi Dengan Komplikasi - santi dwi astuti; Elina Endang (Jurnal Farmasi Indonesia, 2018)
ABSTRACT Hypertension is widely known as cardiovascular disease and is one of the risk factors for chronic renal failure. People with hypertension with kidney disorders occupy the highest incidence rate (35%) compared to hypertension which causes complications in other organs. CRF is a clinical condition characterized by irreversible decline in kidney function. Giving more than one antihypertensive drug can lead to drug interactions (Fitriani, 2007). Research Rahmawati et al. (2006) about a retrospective study of drug interactions in the education hospital of dr. Sardjito Yogyakarta reports that drug interactions that occur in hospitalized patients are 59%. Inpatients found 125 occurrences of drug interactions. The most common antihypertensive drug interactions are a combination of captopril and furosemide. The aim of this study is to describe the antihypertensive treatment in hypertensive patients with CDK along with the therapeutic relevance in terms of the right indication, the right patient, the right dose and the right drug based on JNC VIII. And other studies aim to examine the potential for drug interactions in antihypertensive therapy. The research method used is a type of descriptive research that is non-experimental, data taken retrospectively. The sample of this study were patients diagnosed with hypertension with complications who received combination antihypertensive therapy that met the inclusion and exclusion criteria. The results of the first study showed that the most widely used antihypertensive drugs by patients were loop diuretics, namely furosemide (9.23%). The category of drug accuracy according to JNC VIII was obtained for indication therapy (100%), right for the patient (100%), right for the drug (78.5%) for the right dose (98.46%). The results of the second study showed 31 patients (81.58%) had drug interactions and 7 patients (18.42%) did not experience drug interactions. Of the total 31 patients the potential for the most frequent interactions was moderate 120 (53.6%). The drug that is most used and causes interaction is catapres with diazepam causing moderate interactions Keywords: treatment studies, potential drug interactions, complications with hypertension